A Semantic Analysis of Denotative and Connotative Meanings in the Song “Firework” by Katy Perry - Yolanda Jesica Sitanggang; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
This study investigates the denotative and connotative meanings in the lyrics of Katy Perry’s Firework to reveal how language constructs motivational and symbolic messages. Using a descriptive qualitative method, selected lexical items, phrases, and clauses were analyzed to identify literal meanings and their associative expansions. The results show a semantic trajectory from vulnerability, fragility, and emotional pressure toward self-empowerment, inner potential, and confident self-expression. Words such as plastic bag, paper thin, and house of cards denote fragility but symbolize emotional weakness, while spark, ignite, shine, and firework convey empowerment and individuality. These findings highlight the role of lyrics as a meaningful medium for emotional engagement and personal reflection, emphasizing the significance of semantic analysis in understanding how language shapes listeners’ psychological and symbolic experiences.